Serangan Parlatoria blanchardii Pada Beberapa Varietas Kurma (Phoenix dactylifera L) Di Pembibitan Mapanget Kabupaten Minahasa Utara - Ricky A. Mangudisang; Jimmy Rimbing; Caroulus S. Rante; Adeleyda Lumingkewas (Universitas Sam Ratulangi, 2020)
ABSTRACTP. blanchardii is the major insect pest. Adult and nymph insects, suck nitrogen andmacro elements in leaves. In high-level attacks, P blanchardii causes major damage in the formof decreased P. blanchardii attacks causing date palms to cover a very thick leaf surface so thattranspiration, respiration and photosynthesis are disturbed, causing leaf wilt, inhibiting growthand reduction of mature tree yields and death of trees young. The research was carried out fromNovember 2019 to February 2020 at the Green House of Balit Palma Manado, North Sulawesi.The research method used was RAK with 7 treatments in the form of date varieties and 3replications. This research was conducted by means of quantitative descriptive data collectionmethods or primary data which was carried out directly in the field and saw firsthand P.blanchardii attacks on palm leaves. The things that were observed in this study were, symptomsof P. blanchardii pest attack on date palm leaves, attack on 5 leaflets and 10 leaflets, and 7varieties of date palm attacks per tree. The results showed that the percentage of attacks by P.blanchardii on dates was the highest attack on the Fard variety 55.41% and the lowest attackpercentage was the 9.32% Barhee variety. So it is necessary to do further research on P.blanchardii pests and also control using natural enemies against P. blanchardii pests on datepalms in Indonesia.Keywords: attacks, P. blanchardii, date palm variety